2018
DOI: 10.1098/rspb.2018.0826
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito-borne transmission in urban landscapes: the missing link between vector abundance and human density

Abstract: With escalating urbanization, the environmental, demographic, and socio-economic heterogeneity of urban landscapes poses a challenge to mathematical models for the transmission of vector-borne infections. Classical coupled vector–human models typically assume that mosquito abundance is either independent from, or proportional to, human population density, implying a decreasing force of infection, or per capita infection rate with host number. We question these assumptions by introducing an explicit dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 46 publications
2
49
1
2
Order By: Relevance
“…Micro-scale spatial heterogeneity in transmission intensity and the effects of human movement between neighbourhoods could also explain the rapid re-emergence. Small-scale differences in socioeconomic status and population density between neighbourhoods in a large city can result in different relationships between mosquito and human population sizes, resulting in widespread heterogeneity in R 0 across neighbourhoods [55]. Previous studies of mosquito trap data in the city have demonstrated that neighbourhoods with differing socioeconomic characteristics have different vector population patterns [43].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-scale spatial heterogeneity in transmission intensity and the effects of human movement between neighbourhoods could also explain the rapid re-emergence. Small-scale differences in socioeconomic status and population density between neighbourhoods in a large city can result in different relationships between mosquito and human population sizes, resulting in widespread heterogeneity in R 0 across neighbourhoods [55]. Previous studies of mosquito trap data in the city have demonstrated that neighbourhoods with differing socioeconomic characteristics have different vector population patterns [43].…”
Section: Discussionmentioning
confidence: 99%
“…These indicators are associated with how the territory is occupied by human populations. Hypothesized that areas with higher percentage of human occupation and demographic density are areas with higher risk for the spread of dengue due to the greater proximity between hosts and greater number of breeding sites available for Aedes vectors [27].…”
Section: Construction Of Indicatorsmentioning
confidence: 99%
“…A well defined statistical analysis of the front fluctuations can be then performed by comparing it with a perfectly flat reference. 2 Since the disorder is totally uncorrelated, the front feels different disorder realizations as it moves. This assures the property of self-averaging.…”
Section: The Model and Its Phenomenologymentioning
confidence: 99%
“…The representation of population heterogeneity in spatially explicit epidemic models was listed as one of the most important challenges [1]. Very recent results show that spatial transmission variability is essential to reproduce spatio-temporal propagation patterns emerging from some epidemic data sets [2]. One of the simplest epidemic models for infectious diseases is the deterministic Susceptible -Infected -Recovered (SIR) originally formulated by Kermack and McKendrick [3] in which the individuals are removed from the population either because they die or because they acquire lifelong immunity.…”
Section: Introductionmentioning
confidence: 99%